INCORPORATING SOCIAL DESIGN FOR DISABILITY-INCLUSIVE SOCIAL ENTREPRENEURSHIP: A CATALYST FOR SOCIETAL TRANSFORMATION (Innovation in Woodworking Industry and Engineering design, 2026)
This study uses the potential of social design as a tool to promote social entrepreneurship involving people with disabilities. Social design, with its human-centered, empathic and collaborative approach, is being explored as a key strategy for creating business models that effectively meet the needs and aspirations of people with disabilities. This article uses social design principles and explores how they can be incorporated into social entrepreneurship to promote disability inclusion, improve accessibility and generate socio-economic impact. This approach highlights the need to further explore the unique experiences and requirements of people with disabilities, thereby promoting the development of innovative, tailored solutions.